EFFECT OF BANDELITATION OF IMMAGES ON COMPRESSION BY ALGORITHM SPECK - M., Hettiri*1; Z. E., Baarir1.; A., Ouafi1; A., Taleb-ahmed2 (university of eloued جامعة الوادي, 2019)
The bandelets representation (the bandelitation) effectively gives the contours of the images thanks to the orthogonal bases of bandelets as well as the zones of homogeneous regularity in the form of a residue decomposed in wavelets. The orthonormal framework makes it possible to obtain theoretical results on the approximation capabilities of this representation showing their interest with respect to the two-dimensional separable wavelet bases. However, it remains to confirm these elements by numerical results of compression. We propose in this work a new approach based on the bandelitation effect on the SPECK algorithm "Set Partionning Embedded bloCK". The proposed approach manipulates the coefficients less because it is characterized by additional decorrelations in the exploitation of the geometry of the image.
artical
Keywords: bandelets; contours; geometry of the image.